ANALISIS FAKTOR- FAKTOR YANG BERPENGARUH TERHADAP PEMILIHAN METODE AKUNTANSI PERSEDIAAN PADA PERUSAHAAN WHOLE SALE & RITEL DI BURSA EFEK INDONESIA (BEI) TAHUN 2008 – 2010 (Students' Journal of Accounting and Banking, 2013)
Inventory is activa which the company has for sale in normal business operation or goods to be used or consumed in the production of goods to be sold. The selection method of inventory is important, because every decision has economic consequences. The purpose of this study was to examine the effect of company size, ownership structure, current ratio, financial laverage, the variability of inventory, and the intensity of the selection method of inventory supplies at Whole Sale and Ritel companies that go public on the Indonesia Stock Exchange (BEI). Object of this research is Whole Sale and Retail companies which listed on the Indonesia Stock Exchange (BEI) and publish financial statements in 2008 – 2010. Sampling using purposive sampling method is a method of sampling by specifying certain criteria. The company uses the FIFO method of inventory by 5 samples while companies using the average of 18 samples. Based on the analysis of this research concludes that the results of hypothesis testing using logistic regression find empirical evidence that the factors which influence the choice of inventory method is company size, current ratio, and inventory intensity, while the ownership structure, financial laverage, and the variability of inventory, they’re not a factor determinant in the choice of inventory accounting methods.Keywords: inventory method selection, company size, ownership structure, current ratio, financial laverage, the variability of inventory, inventory intensity